Supply- and demand-side factors in global banking - Mary Amiti; Patrick McGuire; David E. Weinstein (Federal Reserve Bank of New York, 2017)
What is the role of supply and demand forces in determining movements in international banking flows? Answering this question is crucial for understanding the international transmission of financial shocks and formulating policy. This paper addresses the question by using the method developed in Amiti and Weinstein (forthcoming) to exactly decompose the growth in international bank credit into common shocks, idiosyncratic supply shocks, and idiosyncratic demand shocks for the 2000-16 period. A striking feature of the global banking flows data can be characterized by what we term the "Anna Karenina Principle": all healthy credit relationships are alike, but each unhealthy credit relationship is unhealthy in its own way. During non-crisis years, bank flows are well explained by a common global factor and a local demand factor. But during times of crisis flows are affected by idiosyncratic supply shocks to a borrower country's creditor banks. This has important implications for why standard models break down during crises.
Keywords: F34; G01; G21; 330; international banking; global financial crisis; supply shocks versus demand shocks; BIS consolidated banking statistics; Internationale Bank; Kapitalmobilität; Internationales Finanzsystem; Finanzkrise; Schock